Ukraine: The Cyber Battlefield. (12th May 2022) - O'Connor, Patrick
Abstract: The Ukrainian conflict did not start with an invasion. gamified Patrick O'Connor CISSP CEH MBCS explores the many 'trial runs' of cyber attacks leading up to the physical war in Ukraine.